2002
DOI: 10.1037/0022-3514.83.5.1150
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to loss and chronic grief: A prospective study from preloss to 18-months postloss.

Abstract: The vast majority of bereavement research is conducted after a loss has occurred. Thus, knowledge of the divergent trajectories of grieving or their antecedent predictors is lacking. This study gathered prospective data on 205 individuals several years prior to the death of their spouse and at 6-and 18-months postloss. Five core bereavement patterns were identified: common grief, chronic grief, chronic depression, improvement during bereavement, and resilience. Common grief was relatively infrequent, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
654
12
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 760 publications
(763 citation statements)
references
References 94 publications
59
654
12
22
Order By: Relevance
“…When suffering the loss of a loved one, one can feel as if the attendant sadness and longing will last indefinitely. Although successful adaptation to the loss is the most frequent response (Bonnano et al, 2002), grief does not abate in a substantial minority; rather, it develops into Complicated Grief (CG) (Ott, Lueger, Kelber, & Prigerson, 2007). CG, previously known as chronic, pathological or traumatic grief, includes debilitating recurrent pangs of painful emotions, with intense yearning, longing and searching for the deceased, and preoccupation with thoughts of the loved one.…”
Section: Introductionmentioning
confidence: 99%
“…When suffering the loss of a loved one, one can feel as if the attendant sadness and longing will last indefinitely. Although successful adaptation to the loss is the most frequent response (Bonnano et al, 2002), grief does not abate in a substantial minority; rather, it develops into Complicated Grief (CG) (Ott, Lueger, Kelber, & Prigerson, 2007). CG, previously known as chronic, pathological or traumatic grief, includes debilitating recurrent pangs of painful emotions, with intense yearning, longing and searching for the deceased, and preoccupation with thoughts of the loved one.…”
Section: Introductionmentioning
confidence: 99%
“…This might fulfill a buffering function in the process, and as proposed by Fredrickson (1998), might influence the regulation of NA. Interestingly, only about 10% of patients followed the so-called resilient trajectory (Bonanno et al, 2002), i.e. experienced low NA with simultaneously moderate PA (the "no response" subgroup).…”
Section: Discussionmentioning
confidence: 99%
“…In their pivotal research on the subject Bonanno et al (2002) showed that even in a group of people who experience the same event adaptation trajectories are differentiated regarding both their baseline response to the event and further course of responding. Although the cited research and its subsequent replications under various conditions (Bonanno et al, 2008) revealed that in a considerable proportion (about 35-55%) of cases despite an initial decrease in wellbeing the course of adaptation was eventually favorable, nevertheless negative aspects of functioning (such as depression or PTSD) were usually taken under consideration.…”
mentioning
confidence: 99%
“…In modern Western societies, there is a common belief that people will experience intense distress soon after a bereavement and should then get over it relatively quickly (Wortman & Silver, 2001;Bonanno et al, 2002). Other cultures and religions may hold an expectation that the dead will remain an important part of the lives of the living offering opportunities for ongoing remembrance and a sense of connection.…”
Section: Longer Term Adaptation To Bereavementmentioning
confidence: 99%